The Impact of Storytelling on English Language Development in Early Childhood Education - Surya, Ulvia Ika; Pratiwi, Vera Aprilia (PG-PAUD Trunojoyo, 2024)
This study investigates the impact of storytelling on English language development among young children in early childhood education. The subjects of the research include 60 children aged 4-6 years from three different preschools. Data collection methods encompass pre- and post-tests, observation checklists, interviews, and focus groups. Quantitative data were analyzed using paired t-tests and ANOVA, while qualitative data were examined through thematic analysis. The findings reveal significant improvements in vocabulary acquisition, comprehension, and narrative skills, with both traditional and digital storytelling methods proving effective. The novelty of this research lies in its mixed-methods approach and the comparative analysis of traditional and digital storytelling, providing comprehensive insights into their respective impacts on language development.